PP.12.11: DIFFERENCES OF SYMPATHO-VAGAL BALANCE IN RELATION TO DIURNAL/NOCTURNAL BLOOD PRESSURE RATIO IN ESSENTIAL HYPERTENSIVES. (June 2015) - Di Raimondo, D.; Miceli, G.; Tuttolomondo, A.; Butta', C.; Casuccio, A.; Pinto, A.
Abstract : Objective: The extent of the physiological nocturnal dip of blood pressure (BP) and its variation seems to be correlated with autonomic nervous system's (ANS) activity. This relationship is not completely clear, however, especially with regard to the role of the two different components of the ANS and their balance. For example, patients with primary autonomic failure and very low sympathetic and parasympathetic activities also have a high incidence of nondipping, suggesting that it is not the inability to inhibit sympathetic activity during the night, but the inability to modulate autonomic tone that is responsible for the nondipping phenomenon. In order to assess the relationship between ANS's activity and dipping pattern observed by ABPM, we investigated the time domain HRV indexes obtained from 24-hours-Holter ECG monitoring in a group of hypertensive subjects. Design and method: Were enrolled 132 patients with hypertension who have been subjected to an ABPM and to an 24-hours-Holter ECG monitoring to not more than 30 days apart. Time-domain HRV parameters evaluated were the standard deviation of all normal RR intervals (SDNN), the standard deviation of the averaged normal RR intervals for all 5-min segments (SDANN), the root mean square of differences between adjacent R-R intervals (rMSSD) and the percentage of adjacent R-R intervals that varied by more than 50 ms (pNN50). SDNN and SDANN measures estimates sympathetic nervous system (SNS) activity, whereas rmSSD and pNN50 measures estimates parasympathetic nervous system (PNS) activity. Results: We observed a progressive reduction of SDNN and SDANN values from extreme dippers to dippers to nondippers to reverse dippers although the only statistical significance was obtained comparing extreme vs reverse dipper (p: 0.14). We did not observe differences regarding to the PNS activity HRV markers. Conclusions: In our sample non dippers and reverse dippers patients seems to be marked by a change of the sympatho-vagal balance due to increase of SNS activity as assessed by the reduction of SDNN and SDANN parameters.